RISK ASSESSMENT OF AFLATOXIN IN BRAZIL NUT BY PRODUCT CONSUMPTION IN THE AMAZON REGION - KLUCZKOVSKI, ARIANE; VIANA, CIBELE; BARRONCAS, JANAÍNA; LIMA, EMERSON; VALENTIM, CAROLINA; XAVIER, LAWRENCE; CAMPELO, PEDRO; KLUCZKOVSKI, AUGUSTO (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Evaluate exposure to aflatoxins in processed Brazil nut (chopped and sliced) products marketed in Amazonas State. Methods: The samples were purchased during the 2017 harvest at the local retail in the city of Manaus/AM/Brazil in the form of sliced and chopped. Moisture content (MC) and water activity (aw) were verified, aflatoxins (AFB1, AFB2, AFG1, AFG2) were quantified by liquid chromatography. To characterize the risk of exposure to genotoxic use the population margin of exposure (MOE). Results: Chopped and sliced Brazil nut samples analyzed here presented an MC average of 1.62% and water activity of 0.26. These values indicate that samples are safe, according to physical-chemical baselines. Regarding aflatoxins presence, 8% of the samples presented aflatoxins total levels >10 μg/kg. A risk evaluation was performed in which exposure of the population to these substances is observed and, once found; the MOE was 1036 ± 793 (<10 000). Conclusion: Regarding the risk assessment, it was possible to observe that there is a possibility exposure of the population to these substances since the average of MOE found was 1036±793, or <10 000, characterizing this possible risk.